Effects of plyometric training on skill and physical performance in healthy tennis players: A systematic review and meta-analysis - Deng, Nuannuan; Soh, Kim Geok; Huang, Dandan; Abdullah, Borhannudin; Luo, Shengyao; Rattanakoses, Watnawat (Frontiers in Physiology, 2022)
Background: Plyometric training is a highly effective form of training designed to improve sports performance in athletic populations; however, the effects of plyometric training on the skill and physical performance in tennis players are unclear. Methods: The purpose of this systematic review is to determine the effects of plyometric training on the skill and physical performance in tennis players. A systematic electronic literature search was carried out in the databases SCOPUS, PubMed, Web of Science and SPORTDiscus (via EBSCOhost). PICOs extraction tool was used to extract data, which was then summarized using a narrative synthesis approach. The methodological quality of studies was assessed using the PEDro scale. Out of the 365 identified papers, 11 were included in the review with a mean PEDro score of 4.82 (range 3-7). Results: The results revealed that tennis serve (n=5) were the key skill studied in plyometric training interventions; however, there have been few studies that have simultaneously analyzed the speed and accuracy of the serve (n=2). Regarding physical performance, muscular strength (6 studies) and agility (6 studies) were the superior physical ability learned in plyometric training interventions, followed by speed (five studies), power (four studies), and maximal aerobic/reaction time (two studies). Evidence suggests that plyometric training improves muscular strength, agility, speed and power. Furthermore, evidence of insufficient plyometrics exposure demonstrates the effect of plyometric training on maximal aerobic and reaction time. Conclusion: Plyometric training is a feasible training option with the potential for improving tennis serve and various physical performances in tennis players. The tennis serve involves highly complex strokes, which imposes significant shoulders and lowering back loads. Tennis players who do not engage in adequate strength training may sustain injuries. In this respect, plyometric training organizes the body's structural, neurological, and elastic components to achieve greater power output. This conditioning mechanism could help tennis players achieve better service performance. On the other hand, plyometric training provides the stimulus required to train the stretch-shortening cycle mechanism and enhances the explosive contraction of the tennis player. This procedure could help tennis players improve and achieve better physical abilities.